Efficiency of flow-through system for seed production of Tor putitora (Hamilton) at Bhimtal, Kumaon Himalaya - Sehgal, K L; Malik, D S (Indian Journal of Fisheries, 2011)
The golden or Himalayan mahseer (Torputitora),oneof the most thrilling sports fishesin the world, has been classified recently asone of the threatened species of the Himalayanregion and hence needs rehabilitation. Thisinvolves intensive aquaculture of this speciesto produce its seed for planting the streams andlakes. The first attempt which met with successwas made by Tripathi (1977). Attempts ofSehgal and Kumar (1977) and Pathani and Das(1979) met with partial success. Joshi (1981)and Joshi and Sexena (1989) undertook preliminarywork on seed production of T. putitoraat Bhimtal by adopting techniques ofTripathi (1977).